Potentialities of Lettuce (Lactuca Sativa L.) in Hydroponics System Under Simple Nutrient Addition Program (SNAP) - ELIGIO BORRES; EDDIE BASULGAN; RIKKIE MAE DALANON (Camarines Sur Polytechnic Colleges, 2022)
The study was conducted to evaluate the potential of lettuce in a non-recirculated hydroponics system using a simple nutrient addition program (SNAP) in terms of plant height, number of leaves, length of leaves, width of leaves, and yield under screenhouse conditions. The study was conducted at the High Value Commercial Crops (HVCC) production area, DEBESMSCAT, Cabitan, Mandaon Masbate, from February 22, 2021, to March 23, 2021. The experimental design used was the CRD with four (4) treatments and three (3) replications. The study used different levels of SNAP solution. Treatment A used 25ml of SNAP A and SNAP B, Treatment B (30ml), Treatment C (35ml) and Treatment D (Control). The results of the study revealed that the application of SNAP solution to the lettuce did not have a significant effect on the length and width of lettuce leaves. However, the application of SNAP solution to the lettuce had a significant effect on the height, number of leaves, and yield. The different levels of SNAP solution had a highly significant effect on water consumption and the SNAP hydroponics system proved highly efficient in water consumption during the summer season inside the screenhouse under DEBESMSCAT, Masbate condition.